Heteroatom-substituted tetra(3,4-pyrido)porphyrazines: a stride toward near-infrared-absorbing macrocycles - Vachova, Lenka; Machacek, Miloslav; Kučera, Radim; Demuth, Jiri; Cermak, Pavel; Kopecky, Kamil; Miletin, Miroslav; Jedlickova, Adela; Simunek, Tomas; Novakova, Veronika; Zimcik, Petr (Organic & biomolecular chemistry, 2015)
A synthesis procedure for heteroatom-substituted tetra(3,4-pyrido)porphyrazines that absorb light near 800 nm was developed. Based on the observed relationships between the structure and photophysical parameters, a novel highly photodynamically active (IC50 = 0.26 μM) compound was synthesized and biologically characterized.
Keywords: vztahy mezi strukturou a aktivitou; Molecular Structure; fotochemie; Light; Macrocyclic Compounds; Structure-Activity Relationship; molekulární struktura; blízká infračervená spektroskopie; makrocyklické sloučeniny; světlo; Photochemistry; Porphyrins; porfyriny; Spectroscopy, Near-Infrared